Lipid biomarker as indicator for assessing the input of organic matters into sediments and evaluating phytoplankton evolution in upper water of the East China Sea. (June 2019) - Chen, Jianlei; Li, Feng; He, Xiuping; He, Xingliang; Wang, Jiangtao
Graphical abstract: Highlights: OMs input from both terrestrial and marine in the East China Sea were indicated by Lipid biomarkers. Fatty acids indicated that marine input dominated much more with intensified eutrophication. Lipid biomarkers recorded the structure of phytoplankton community overlying. Bra/Din was a critical indicator for inversion of phytoplankton community structure. Complex red tides composed of diatoms and dinoflagellates tended to form. Abstract: It is meaningful and challenging to differentiate the origination of organic matters (OMs). As a kind of geochemical index, lipid biomarkers reflected the changes in the source of OMs in marine sediments caused by intensified eutrophication. In this study, the composition and distribution of lipid biomarkers (fatty acids and fatty alcohols) in sediment core were determined to distinguish the origination of different OMs in the condition of intensified eutrophication in the East China Sea. The source apportionment of δ 13 CTOC (–22.03∼–23.81‰) and C/N ratio suggested that the source of OMs was a mixture of terrestrial and marine, and mainly from the marine input. The fatty acids (total content between 1.69 and 9.48 μg g −1 ) showed typical bimodal distribution which indicated terrestrial-marine mixed input and especially from autogenic marine input, and marine phytoplankton contribution increased in sediment in past decades. The principal component analysis (PCA) also indicated that most of the fatty acids were controlled by marine and terrestrial, and marine input (algae and bacteria) was the main source (>75%). The total content of the fatty alcohols ( n -alkanol and sterol) ranged from 2.1 μg g −1 to 29.9 μg g −1 and they were derived from terrestrial and marine input half to half. The phytoplankton community in upper water reconstructed based on Bra/Din ratio was consistent with the trend that single diatom-red tides turned into complex red tides composed of diatoms and dinoflagellates from the 1980s of the last century.